Photoelectrochemical Methanol Oxidation by TiN Nanoparticles Supported on TiO2. (19th June 2018) - Baturina, Olga A; Epshteyn, Albert; Simpkins, Blake
Abstract : Photocatalytic activity of TiO2 -supported TiN and Au nanoparticles towards methanol oxidation is investigated under both visible and UV light excitation. We demonstrate that the TiN/TiO2 photocatalyst performs better than the Au/TiO2 under visible excitation at potentials more positive than 0.1 V vs a Ag/AgCl reference electrode. Under UV excitation, photocurrent enhancement is observed for both the TiN/TiO2 and the Au/TiO2 photocatalysts in the entire potential region from -0.6 to 0.5 V, as compared to pure TiO2 . The photocurrent enhancement under UV excitation was assigned to (1) better charge separation in the Au/TiO2 photocatalyst, and (2) generation of highly reactive holes due to interband transitions in TiN and Au nanoparticles.